Confining MoS2/C nanoparticles on two-dimensional graphene sheets for high reversible capacity and long-life potassium ions batteries. (1st February 2023) - Li, Jing; Hu, Feng; Wei, Hui; Hei, Jinpei; Yin, Yanjun; Liu, Guoan; Wang, Nannan; Wei, Hehe
Abstract: Benefiting from the unique layer structure and large interlayer spacing, the transition metal dichalcogenides have been regarded as promising anode materials to host K ions and widely explored in potassium ion batteries (PIBs). However, the low conductivity and large volume variation decline the cycling capacity and stability. It is still challenge to develop high performance anode to storage K + . Herein, the MoS2 nanoparticles anchored onto graphene sheet were synthesized (MoS2 –C/rGO) through facile "one-step redox reaction" and following sulfidation method. Impressively, MoS2 –C/rGO displayed superb cycling capability with a high reversible capacity of 405.25 mAh/g after 100 cycles at 0.1 A/g, accompanied with remarkable rate performance, outperforming than MoS2 –C and MoS2 . Most importantly, the ultra-long working life over 2000 cycles with a stable capacity of 161.67 mAh/g at 2 A/g was achieved in MoS2 –C/rGO. The two-dimensional structure, rGO sheet and N, P co-doped C matrix of MoS2 –C/rGO play great role on providing abundant ions storage sites, increasing conductivity and suppressing volume expansion, leading to high specific capacity, superior rate performance and cycling stability in PIBs. The ex-situ XPS revealed the conversion reaction mechanism for MoS2 during cycling. Accordingly, our work provides a new insight to design alternative anodes for PIBs and is significant to the application of the new generation secondary batteries. Graphical abstract: Image 1 Highlights: The MoS2 nanparticles mixed with N, P co-doped C matrix were confined on to the graphene sheet unifromly. The ultra-long life span over 2000 cycles in high rate of 2 A/g with a high reversible capacity was achieved. The ex-situ XPS results verifies the reversible reaction and conversion mechanisms during potassiation/depotassiation process.